Objectives of community policies and programs associated with more healthful dietary intakes among children: findings from the Healthy Communities Study. (19th June 2018) - Webb, K. L.; Hewawitharana, S. C.; Au, L. E.; Collie‐Akers, V.; Strauss, W. J.; Landgraf, A. J.; Nagaraja, J.; Wilson, D. K.; Sagatov, R.; Kao, J.; Loria, C. M.; Fawcett, S. B.; et al.
Summary: Background: Rational planning of community policies and programs (CPPs) to prevent obesity requires an understanding of CPP objectives associated with dietary behaviours. Objective: The objective of the study is to identify objectives of CPPs associated with healthful dietary behaviours. Methods: An observational study identified 4026 nutrition CPPs occurring in 130 communities in the prior 6 years. Dietary intakes of fruits and vegetables, added sugar and sugar‐sweetened beverages, among others, were reported among 5138 children 4–15 years of age from the communities, using a Dietary Screener Questionnaire with children age 9 years and older (parent assisted) or parent proxies for younger children. CPPs were documented through key informant interviews and characterized by their intensity, count, and objectives including target dietary behaviour and food environment change strategy. Associations between dietary intakes and CPP objectives were assessed using hierarchical statistical models. Results: CPPs with the highest intensity scores that targeted fast food or fat intake or provided smaller portions were associated with greater fruit and vegetable intake (0.21, 0.19, 0.23 cup equivalents/day respectively with p values <0.01, 0.04, 0.03). CPPs with the highest intensity scores that restricted the availability of less healthful foods were associated with lower child intakes of total added sugar (−1.08 tsp/day, p  < 0.01) and sugar from sugar‐sweetened beverages (−1.63 tsp/day, p  = 0.04). Similar associations were observed between CPP count and dietary outcomes. No other significant associations were found between CPP target behaviours or environmental strategies and dietary intakes/behaviours. Conclusion: CPPs that targeted decreases in intakes of less healthful foods and/or aimed to modify the availability of less healthful foods and portions were associated with healthier child dietary behaviours. Abstract : What is already known about this subject: Community programs and policies (CPPs) use a range of strategies to prevent obesity, based on 'practice tested' models and those with emerging evidence about their success. Yet, understanding the relationship of types and features of CPPs that contribute to success of CPPs, including program and policy objectives in the context of the whole community effort, would inform rational planning for obesity prevention. What this study adds: We studied dietary intakes of 5138 children 4–15 years of age and objectives of CPPs (dietary behaviours targeted and food environment change strategies) in a diverse sample of 130 communities across the USA. We found significant associations between CPPs that aimed to modify community food environments (by restricting availability of less healthful foods and beverages and instituting smaller portion sizes) and higher fruit and vegetable (FV) intake as well as lower sugar and sugar‐sweetened beverage intake. We also found associations between CPPs that targeted less healthful dietary behaviours (fat, fast food) with higher child FV intake. Yet, dietary intakes of interest were not generally consistent with the dietary targets reported by CPPs, e.g. those targeting FV were not associated with higher intakes of FV. Our findings suggest potential benefits from a greater focus of CPPs on food environments. Further evaluation is recommended to identify causal relationships between objectives of CPPs and child diets, and which combinations of CPP objectives are most successful. This article is part of the supplement: The Healthy Communities Study: Examining Community Programs, Policies and Other Characteristics in Relation to Child Weight, Diet, and Physical Activity